Implementation of Learning Innovations in Society 5.0 to Stimulate Creative Thinking Skills at Higher Education - Susanto, Andri Mardi; Epriliyana, Nike Norma; Utama, Hanif Hadinata (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2024)
The high need for the internet for reference is increasingly changing student learning patterns. In the era of Society 5.0, learning models need innovation to keep up with technological developments.  This study aims to describe the influence between Society 5.0 learning innovations on creative thinking skills in higher education. Respondents in this study amounted to 50 students from the Accounting, Management and Economic Education Study Programs who took the Introduction of Management course. The data collection technique used an e-questionnaire. Data analysis using multiple linear regression analysis. The results showed that  learning innovations of Society 5.0 consisting of learning model innovations; learning media innovations; learning strategy innovations; and assignment innovations had an effect on student creative thinking skills.